EFISENSI PENGOLAHAN LIMBAH CAIR HOTEL MENGGUNAKAN MOVING BED BIOFILM REACTOR (MBBR) - Dhuhan Dhuhan; Laili Fitria; Ulli Kadaria (Jurnal Teknologi Lingkungan Lahan Basah, 2021)
Abstract The increase in the number of hotels in Pontianak City has a impact, namely the increase in the generation of wastewater. The hotel wastewater treatment process is widely used by hotels in Pontianak, especially at the Aston hotel, which already has a sewage treatment plant with suspended biological treatment. The processed water often does not meet the quality standards of wastewater which may be disposed of in accordance with PERMEN/LH/68/2016 concerning domestic wastewater quality standards. In this study, the parameters measured were BOD, TSS and pH. The purpose of this study was to determine the efficiency of Aston hotel wastewater treatment using an attached reactorMBBR (moving bed biofilm reactor) with Kaldnes K3 media in reducing BOD and TSS parameters. Growing microorganisms and biofilms on adhesive media for 14 days. Giving Kaldnes K3 adhesive media as much as 30%. Based on the research results of Aston hotel wastewater treatment with attached reactor MBBR able to reduce BOD and TSS parameters. Best lowering efficiency in attached reactor MBBR with the best time of 7 days was able to reduce the BOD parameter from 109.81 mg/L became 7.28 mg/L with an efficiency of 93.37%, and the TSS parameter decreased from the initial concentration of 78 mg/L to 8 mg/L and the efficiency was 89.74%.  Keywords : BOD, Kaldnes, Hotel Waste Waste, MBBR, TSS Abstrak Peningkatan jumlah hotel di Kota Pontianak memberi dampak, yaitu meningkatnya timbulan limbah cair. Proses pengolahan air limbah hotel banyak digunakan hotel-hotel di Pontianak. Hotel Aston telah memiliki instalasi pengolahan limbah dengan pengolahan biologi tersuspensi. Air hasil olahannya sering kali belum memenuhi baku mutu air limbah yang boleh dibuang sesuai dengan PERMEN/ LH/ 68/ 2016 tentang baku mutu air limbah domestik. Pada penelitian ini parameter yang diukur yaitu BOD, TSS dan pH. Tujuan dari penelitian ini adalah untuk mengetahui efisiensi pengolahan limbah cair hotel Aston menggunakan reaktor terlekat MBBR (moving bed biofilm reactor) dengan media Kaldnes K3 dalam menurunkan parameter BOD dan TSS. Dilakukan penumbuhan mikroorganisme dan biofilm pada media lekat K3 selama 14 hari. Pemberian media lekat Kaldnes K3 sebanyak 30% dari volume reaktor. Berdasarkan hasil penelitian, pengolahan limbah cair hotel Aston dengan reaktor terlekat MBBR mampu menurunkan parameter BOD dan TSS. Efisiensi penurunan terbaik pada reaktor terlekat MBBR dengan waktu 7 hari, mampu menurunkan parameter BOD dari 109,81 mg/L menjadi 7,28 mg/L dengan efisiensi 93,37 %, dan penurunan parameter TSS dari konsentrasi awal 78 mg/L menjadi 8 mg/L (efisiensi 89,74%). Kata Kunci : BOD, Kaldnes, Limbah Cair Hotel, MBBR, TSS.